Sustainable Development in Rural Ghana - Armstrong, Mira (Consilience, 2013)
Since 2004, Columbia students have been partnering with Obodan, a rural farming village in western Ghana, to develop and implement engineering solutions to problems like water distribution and sanitation. The overarching organization, Engineers Without Borders USA (EWB), has been supervising both the technical details of the projects as well as the community development and adoption thereof, as it does for hundreds of similar projects around the world. Working in Obodan with my classmates and EWB has been the defining experience of my time as an undergraduate, as we learn the possibilities and limitations of engineering, the joys and pitfalls of development work, and how we can carry these lessons throughout our personal and professional lives. This photo essay aims to describe the activities of a typical EWB trip and reflect on the role our work plays in sustainable development.